2014
DOI: 10.1007/s00167-014-3110-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of knee extensor open kinetic chain resistance training in the ACL-injured knee

Abstract: Randomised controlled trial, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
(55 reference statements)
0
6
0
3
Order By: Relevance
“…The literature also agrees that strengthening the thigh muscles' muscles reduces anterior knee laxity [18,19].…”
Section: Discussionmentioning
confidence: 59%
“…The literature also agrees that strengthening the thigh muscles' muscles reduces anterior knee laxity [18,19].…”
Section: Discussionmentioning
confidence: 59%
“…The literature also agrees that strengthening the muscles of the thigh muscles reduces anterior knee laxity (18,19) Also, a study by Barcellona et al (18) showed the results of an OKC knee strengthening program.…”
Section: Discussionmentioning
confidence: 68%
“…All the participants exposed to stimulation were able to complete addition repetitions; ES = 4 ± 2 and MS = 7 ± 6, range (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). No significant difference between the number of additional repetitions for the ES and MS groups were observed (p = 0.187) ( Figure 5).…”
Section: Resultsmentioning
confidence: 91%
“…Resistance training is frequently used to promote muscle hypertrophy, strength and knee laxity. Electrical stimulation (ES) and magnetic stimulation (MS) have been used as an adjunct to athletic training [1][2][3], although it is more commonly used as a rehabilitation therapy to promote quadriceps strength after surgery [4][5][6][7], quadriceps hypertrophy [8], to investigate different types of muscle fatigue [9], daily functional activities after stroke [10], and osteoarthritis patients [11,12]. However, the evidence concerning the usefulness of peripheral stimuli as an adjunct to training programmes for enhancing muscle hypertrophy, strength, knee laxity and training healthy people is not conclusive.…”
Section: Introductionmentioning
confidence: 99%